Kepuasan Masyarakat terhadap Layanan Publik Kantor Pelayanan Pajak Daerah Kepulauan Riau - Ely Kartikaningdyah (Politeknik Negeri Batam, 2015)
Satisfaction of public services is necessary to assess and evaluate the performance of employees in charge directly with the public. To support this routine monitoring work done by identifying the problems that occur in the environment of public agencies. Service users have the right to lodge complaints for services that are not in accordance with standard operating procedures and minimum service standards that have been established by public service agencies, especially at the Regional Tax Office (KPPD) Riau Islands Province. Lack of performance evaluation is expected to increase the satisfaction of both public services and facilities of the service infrastructure. This study aims to measure community satisfaction index for services rendered by employees KPPD Riau Islands. The method used is quantitative descriptive statistics to measure public satisfaction index, based on a decision of the Minister of Administrative Reform No.Kep. / 25 / M.PAN/2/2004. Respondents of this research is the service users taxpayer motor vehicle and samples were taken with the period of 2012-2014 in Riau Islands KPPD which is KPPD Batam, Bintan KPPD, KPPD Tanjungpinang, KPPD Karimun, KPPD KPPD Lingga and Natuna. Results of this study was overall KPPD Riau Islands providing good performance